Readiness for E-Tendering in the Construction Sector- Designing a Computer Programme - Abdul Razaq Hilmi, Reem Rafea; Breesam, Hatem Kh.; Saleh, Azhar H. (Salehan Institute of Higher Education, 2019)
Development of a country is measured by the number and quality of modern and contemporary projects that have been and are being established. As the construction industry is the nucleus for the development of any country, the stages of each project are tracked and monitored. It was found that the procurement stage has the biggest and most important influence in the successful completion of the project with the desired results. This research aims to eliminate corruption in the procurement process, identify theÂ additional factors relating to a contractorâ€™s qualification that contribute towards an increase in the quality of the project; designing a computer programme that conducts the tender process electronically to avoid any human contact. The researcher designed a questionnaire which contains a number of factors that would increase the efficiency and quality of the project. The researcher distributed 50 questionnaire forms and received back 46 completed forms. The questionnaire outputs were analyzed by using the SPSS software which can be defined as a software package used in statistical analysis for data. After analyzing the results a nominal group session was held. This consisted of eight employees with technical, financial, legal, and supervisory and IT expertise. The work was collective and many questions were asked. All relevant factors were discussed. It was agreed to cancel three factors only as being irrelevant to the contractor's qualification process. The most significant findings were that if the organizations adopt the E-T system in the tendering process, corruption cases will disappear, the tendering process will be achieved with high level of integrity and transparency, and in order to implement the E-T system, the organization must be ready to change, the employees should have enough courage to adopt the system, and there would be a need for at least one person to play the role of champion/leader.